7
$\begingroup$

Suppose $G$ is a group. $\{X_n\}_{n = 1}^{\infty}$ is a sequence of i.i.d. random elements of $G$ satisfying the condition that

$$\forall H \leq G, \qquad P(X_1 \in H) = \begin{cases} \frac{1}{[G:H]} & \quad \text{if $[G:H]$ is finite}\\ 0 & \quad \text{if $[G:H]$ is infinite} \end{cases}$$

Is it true that

$$\lim_{n \to \infty} P(\forall i,j\leq n, \ [X_i, X_j] = e)^{\frac{1}{n}} = P(X_1 \in Z(G)) \ ? $$

What have I tried so far?

If we accept an additional supposition, that the events $\{\forall i \leq p, \ X_i \in C_G(X_p) \}$ and $\{\forall i \leq q, \ X_i \in C_G(X_q) \}$ are independent for any natural $p \neq q$. Then we can see, that

$$P(\forall i,j\leq n, \ [X_i, X_j] = e) = \prod_{i = 1}^{n} P(\{\forall j \leq i, \ X_j \in C_G(X_i) \}).$$

Now, let’s see, that on one hand

\begin{align*} &P(\{\forall j \leq i, \ X_j \in C_G(X_i) \}) \\ &= P(X_i \in Z(G)) + (1 - P(X_i \in Z(G))P(X_1 \in C_G(X_i))^{i - 1} \\ &\leq P(X_1 \in Z(G)) + (1 - P(X_1 \in Z(G))\left(\frac{1}{2}\right)^{i - 1} \\ &= \frac{1}{2^{i - 1}} + \left(1 - \frac{1}{2^{i - 1}}\right)P(X_1 \in Z(G)) \\ &= P(X_1 \in Z(G))\left(1 - \frac{1}{2^{i - 1}} + \frac{1}{2^{i - 1}P(X_1 \in Z(G))}\right) \end{align*}

and on the other hand

\begin{align*} &P(\{\forall j \leq i, \ X_j \in C_G(X_i) \}) \\ &= P(X_i \in Z(G)) + (1 - P(X_i \in Z(G))P(X_1 \in C_G(X_i))^{i - 1} \\ &\geq P(X_1 \in Z(G)) + (1 - P(X_1 \in Z(G))P(X_1 \in Z(G))^{i - 1} \\ &= P(X_1 \in Z(G))^{i - 1} + \left(1 - P(X_1 \in Z(G))^{i - 1}\right)P(X_1 \in Z(G)) \\ &= P(X_1 \in Z(G))\left(1 - P(X_1 \in Z(G))^{i - 1} + P(X_1 \in Z(G))^{i - 2}\right) \end{align*}

So, we have

\begin{align*} &P(X_1 \in Z(G)) \\ &= \lim_{i \to \infty} P(X_1 \in Z(G))\left(1 - P(X_1 \in Z(G))^{i - 1} + P(X_1 \in Z(G))^{i - 2}\right) \\ &= \lim_{n \to \infty} \left( \prod_{i = 1}^n P(X_1 \in Z(G)) \left(1 - P(X_1 \in Z(G))^{i - 1} + P(X_1 \in Z(G))^{i - 2} \right) \right)^{\frac{1}{n}} \\ &\leq \lim_{n \to \infty} P(\forall i,j\leq n, \ [X_i, X_j] = e)^{\frac{1}{n}} \\ &\leq \lim_{n \to \infty} \left( \prod_{i = 1}^n P(X_1 \in Z(G)) P(X_1 \in Z(G)) \left(1 - \frac{1}{2^{i - 1}} + \frac{1}{2^{i - 1}P(X_1 \in Z(G))} \right) \right)^{\frac{1}{n}} \\ &= \lim_{i \to \infty} P(X_1 \in Z(G))\left(1 - \frac{1}{2^{i - 1}} + \frac{1}{2^{i - 1}P(X_1 \in Z(G))} \right) \\ &= P(X_1 \in Z(G)). \end{align*}

However, I do not know how to prove that the events in our supposition are always independent (or is there a counterexample?). And neither do I know, how to prove the main statement of the question without using the aforementioned supposition.

$\endgroup$
  • 1
    $\begingroup$ The events are not independent, they can't be. $\endgroup$ – zhoraster Feb 19 '19 at 8:38
5
$\begingroup$

I believe $S_3$ is a counterexample. Let $H< S_3$ be the unique subgroup of index $2$. Then $H$ is abelian, and for every $n$ we have $$P(\forall i,j:[X_i,X_j]=e)^{1/n} \geq P(\forall i: X_i\in H)^{1/n}=\frac{1}{2}.$$ This means the limit on the left (if it exists) is at least $1/2$. On the other hand, $Z(S_3)=\{e\}$, so $P(X_1\in Z(S_3))=P(X_1=e)=1/6$.

For general $G$, a similar argument should show that $$ \liminf_{n\to\infty}P(\forall i,j\leq n:[X_i,X_j]=e) \geq \max_{\substack{H\leq G\\H\text{ abelian}}}\frac{1}{[G:H]}. $$

| cite | improve this answer | |
$\endgroup$
2
$\begingroup$

For finite $G$, the bound given in Julian Rosen's answer is the exact limit, i.e. I claim that $$ \mathrm P(\forall i,j\le n,\ [X_i,X_j] = e)^{1/n}\to \max_{\text{abelian }H \le G}\frac{1}{[G:H]} = \max_{\text{abelian }H \le G}\mathrm P(X_1 \in H). \tag{$\ast$} $$

Indeed, denoting by $\mathcal A$ the collection of abelian subgroups of $G$, $$ \limsup_{n\to \infty} \mathrm P(\forall i,j\le n,\ [X_i,X_j] = e)^{1/n} \le \limsup_{n\to \infty}\biggl(\sum_{H\in \mathcal A} \mathrm P(\forall i\le n,\ X_i\in H)\biggr)^{1/n} =\\ = \limsup_{n\to \infty}\biggl(\sum_{H\in \mathcal A} \mathrm P(X_1\in H)^n\biggr)^{1/n} = \max_{H\in \mathcal A} \mathrm P(X_1\in H). $$

Since by Julian Rosen's answer, $$ \liminf_{n\to \infty} \mathrm P(\forall i,j\le n,\ [X_i,X_j] = e)^{1/n}\ge \max_{H\in \mathcal A}\mathrm P(X_1 \in H), $$ we arrive at $(\ast)$.


In order for (a modification of) the argument to work, it is enough to assume that for some $n\ge 1$, $\sum_{H\in \mathcal A^*} \mathrm P(X_1\in H)^n<\infty$, where $\mathcal A^*$ is the collection of all maximal abelian subgroups of $G$.

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.